BTRFS vs Ext4: Filesystems Impact on Energy Consumption of eMMC-Based Embedded Computers - Jacomelli, Brenda; Bruschi, Sarita Mazzini (Anais do Workshop on Sustainable Computing and Technology Reuse (SCoRe); 2025: Anais do I Workshop on Sustainable Computing and Technology ReuseDO - 10.5753/score.2025.17121, 2025)
Advancements in microelectronics have expanded embedded systems’ capacities, with a significant number now incorporating processing units supporting Linux-based distributions. In energy-constrained environments, selecting an energyefficient filesystem for embedded devices is imperative, yet many performance evaluations focus solely on their time efficiency. To overcome these limitations, this paper proposes a performance evaluation on eMMC-based embedded computers to understand the impact of different filesystems on their energy consumption. We generated a basic Linux image and copied it to the eMMC storage twice. For each copy, we formatted the root filesystem partition with different filesystems (EXT4 and BTRFS) and conducted file operation benchmarks. Measurements of mean power during each benchmark execution were performed by an external microcontrolled device. From the results, it can be inferred that EXT4 is the best overall option for power saving when executing file operations.